(untitled) (GAIMS Journal of Medical Sciences, 2024)
Background: An extremely rare kind of hernia is the traumatic abdominal hernia. It is frequently misdiagnosed, and diagnosing it calls for a high degree of suspicion. Case history: Following a collision with a scooter and a blow to his abdomen from one of the handles, a 40-year-old man was brought to the emergency room complaining of abdominal pain. A left lower abdominal wall hernia was suggested by USG-eFAST. Hernioplasty with meshplasty was performed on the patient. Results: There were no complications following surgery. Conclusions: When a patient is diagnosed with a traumatic abdominal wall hernia, they should have a thorough examination to rule out early signs of organ damage and then have their abdomens radiologically examined to check for intra-abdominal injuries. The diagnosis and treatment of these cases still depend heavily on clinical examination and judgment. Given the possibility of the bowel loop becoming incarcerated, the definitive course of treatment, in this case, is surgical exploration combined with the primary repair of the defect.